tpo3 and dur3, Aspergillus fumigatus Plasma Membrane Regulators of Polyamines, Regulate Polyamine Homeostasis and Susceptibility to Itraconazole - Chen, Mingcong; Zhong, Guowei; Wang, Sha; Zhu, Jun; Tang, Lei; Li, Lei (Frontiers in Microbiology, 2020)
Aspergillus fumigatus is a well-known opportunistic pathogen that causes invasive aspergillosis (IA) infections, which have high mortality rates in immunosuppressed individuals. Long-term antifungal drug azole use in clinical treatment and agriculture results in loss of efficacy or drug resistance. Drug resistance is related to cellular metabolites and the corresponding gene transcription. In this study, through untargeted metabolomics and transcriptomics under itraconazole (ITC) treatment, we identified two plasma membrane-localized polyamine regulators tpo3 and dur3, which were important for polyamine homeostasis and susceptibility to ITC in A. fumigatus. In the absence of tpo3 and/or dur3, the levels of cytoplasmic polyamines had a moderate increase, which enhanced the tolerance of A. fumigatus to ITC. In comparison, overexpression of tpo3 or dur3 induced a drastic increase in polyamines, which increased the sensitivity of A. fumigatus to ITC. Further analysis revealed that polyamines concentration-dependently affected the susceptibility of A. fumigatus to ITC by scavenging reactive oxygen species (ROS) at a moderate concentration and promoting the production of ROS at a high concentration rather than regulating drug transport. Moreover, inhibition of polyamine biosynthesis reduced the intracellular polyamine content, resulted in accumulation of ROS and enhanced the antifungal activity of ITC. Interestingly, A. fumigatus produces much lower levels of ROS under voriconazole (VOC) treatment than under ITC-treatment. Accordingly, our study established the link among the polyamine regulators tpo3 and dur3, polyamine homeostasis, ROS content, and ITC susceptibility in A. fumigatus.